PENGAWETAN LIMA BELAS JENIS KAYU IRIAN JAYA SECARA RENDAMAN DINGIN - Sasa Abdurrohim; Abdurahim Martawijaya; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1987)
Fifteen  wood species from  Irian  Jaya  with sample  test pieces  measuring  5 x 5 x  60 cm,  and  water content  from 20. 0-21.4 percent, were subjected  to cold soaking  treatment,  using 5 and 10 percent  concentration  of BFCA  preservative,  for  three, five  and seven  days. Taking into account  the penetration  and retention  requirement for  wood use condition  under roof and outdoor,  without ground contact,  the result indicates that matoa  wood could not be treated  with the schedule proposed  in this paper.  The other fourteen   wood species could be treated with any of the treatment schedule (Table 4). However,  two species (honggimako  and senai) meet only the requirement for  use under roof  without ground  contact.